The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/ijc.31298
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactive gp130/STAT3‐driven gastric tumourigenesis promotes submucosal tertiary lymphoid structure development

Abstract: Tertiary lymphoid structures (TLSs) display phenotypic and functional characteristics of secondary lymphoid organs, and often develop in tissues affected by chronic inflammation, as well as in certain inflammation‐associated cancers where they are prognostic of improved patient survival. However, the mechanisms that govern the development of tumour‐associated TLSs remain ill‐defined. Here, we observed tumour‐associated TLSs in a preclinical mouse model (gp130 F/F) of gastric cancer, where tumourigenesis is dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 48 publications
0
42
0
Order By: Relevance
“…Hyperactivation of STAT3 signaling promotes both gastric tumorigenesis and lymphoid tissue formation. 14 It is possible that hostderived EVs in H pylori infection represent yet another mechanism by which the bacterium mediates inflammation.…”
mentioning
confidence: 99%
“…Hyperactivation of STAT3 signaling promotes both gastric tumorigenesis and lymphoid tissue formation. 14 It is possible that hostderived EVs in H pylori infection represent yet another mechanism by which the bacterium mediates inflammation.…”
mentioning
confidence: 99%
“…These findings showed that IL6ST might be the direct downstream target of PLXNC1. IL6ST (also known as GP130) controls the IL-6/STAT3 signaling pathway and accelerates gastric tumorigenesis (14,15). We performed ChIP-qPCR and found PLXNC1 was enriched on the IL6ST promoter (Figure 5C), further identifying the expressional control of IL6ST by PLXNC1 under a DNA lever.…”
Section: Plxnc1 Regulates Il6st Expression At the Dna Level In Gc Cellsmentioning
confidence: 88%
“…In gastric cancer, high expression of CCL21 in tumor tissues was correlated with tumor invasion and lymph node metastasis [22] . Induction of CCL21 was found in tertiary lymphoid structures which participated in development of inflammation-associated cancer in spontaneous gastric tumorigenesis model [23] . For immune cells, CCL21 can induce several processes of immune response activation including co-localization and recruitment of T cells and dendritic cells; improving cell migration; co-stimulation of naïve T cell expansion and Th1 polarization [21] .…”
Section: Discussionmentioning
confidence: 98%